We are Wu: assessing Chinese fans' socio-cultural identification with the only Chinese footballer in a top European league. Issue 4 (4th July 2021) - Shen, Huawen James; Yan, Libo; Ye Haobin, Ben; Yan, Qi
ABSTRACT: This study examined how Chinese football fans identify themselves with Lei Wu, currently the only Chinese footballer playing in a European mainstream league. Chinese fans' social media posts about Wu were compared after scoring vs. not scoring, and after playing vs. playing, in several matches in a row. Qualitative (content analysis) and quantitative (chi-square tests) analyses were conducted. Two major dimensions of identification with Wu emerged, namely athletic (identification with Wu's athleticism) and socio-cultural (identification with Wu as a Chinese icon). There was stronger socio-cultural identification with Wu when he scored goals, but this aspect of identification did not vary based on whether or not he made league appearances. The study makes a unique contribution by studying fandom as a mechanism for expressing cultural pride. The results are discussed in terms of the cultural and policy contexts of contemporary China.